MENAFSIR AYAT EKONOMI DALAM AL-QUR’AN: Dari Teks Hingga Konteks - Riki Febri Ramdhani (Prodi. Hukum Ekonomi Syariah, Fakultas Syariah, IAI Hamzanwadi Pancor Lombok Timur, 2022)
Abtract This paper talks about the Economic verses contained in the Qur'an. The author uses the literature study method to dig up information about the main theme. In addition, the author also uses Abdullah Saeed's contextual approach to interpret these verses. After going through a long process, the author finds that the Qur'an instructs its adherents to act fairly and equally in every economic process, both in the process of production, consumption and distribution. In terms of consumption, the Qur'an encourages us to eat or buy products that are lawful and good, as the meaning of Q.S. al-Baqarah verse 168. In the current era of consumerism and the digital era, the instructions of the Qur'an must be contextualized in everyday life as Abdullah Saeed said. Not only that, halal food certainly comes from a halal and good production and distribution process.